Developing Task Based Learning Materials Model for Translation Course - Yanuarti Apsari; Setya Resmini; Yana Yana (STAI Hubbulwathan Duri, 2022)
This research was a pilot study which intended to develop Task based learning materials model for the Translation course. The study employed Research and Development. The research procedure of this study was adapted from Borg and Gall (1983). There are only three out of ten steps were employed: research and information collecting, planning, and developing preliminary form of product. The respondents of this research were two lecturers and third-semester students of the English education study program in a university in Cimahi. The data was taken from questionnaire and interviews. The research findings show that (1) from the analysis result, most of respondents wanted the learning materials that suits their need and interest. Thus, the pilot product covered eight topics such as translation process, a good translation, translation method, idiomatic translation, figurative language, simile and metaphor, direct technique and indirect technique; (2) the design used task-based learning model and was made based on three sessions namely pre-task, task cycle and language focus; (3) The translation material in pre activity consists of brainstorming and introducing the topics. While, translation materials in task cycle involves translating various sources such as newspaper, novel, poem, song lyric, film review and abstract. The last, teaching materials in language focus deal with grammar session. Since this research is pilot study, thus, the results need to be validated by expert judgement. Furthermore, it is recommended to apply the product in the real class.